Governance for SME Sustainability and Growth - Ryabota, Vladislava (International Finance Corporation, Washington, DC, 2019)
As small and medium enterprises (SMEs) evolve from start-up to maturity, they need to grow into governance. This paper introduces the International Finance Corporation (IFC) governance methodology for SMEs, a governance model designed to support the organic growth of small and mid-size businesses by offering solutions that are fit for purpose through each stage of their evolution.